The resilient economic impact of CPEC and future of MNCs: Evidence from Pakistan - Anwar, Syed Umair; Wuyi, Zhang; Ali Shah, Syed Zahid; Ullah, Qudrat; Amir, Syed Muhammad; Syed, Ammara (Frontiers in Environmental Science, 2022)
The purpose of this study is to analyze the resilient economic impact of CPEC on Pakistan and the future of MNCs. The present study was conducted in Pakistan and Southeast China and explored how infrastructure development under the CPEC is useful for the socio-economic development of Pakistan, as well as what kinds of policies Pakistan should develop and apply for the multi-billion dollar CPEC project to improve the socio-economic paradigm of Pakistan. A sample of 274 respondents was selected through a multistage sampling technique from across Pakistan and Southeast China in an approximately one-month period. An online survey questionnaire and a one-on-one interview were used to collect primary data from the respondents. The data was further processed and analyzed with the statistical software SPSS 26, which employed Cronbach's Alpha, the Kaiser-Meyer-Olkin & Bartlett's test, and total variance explained. The results of the study show that the CPEC is a catalyst for Pakistan to improve its socio-economic conditions and achieve sustainable development. Moreover, the study reveals that the megaproject aims to develop Pakistan’s infrastructure and transportation network, cover the energy crisis, increase trade and employment, and build Gwadar port and special economic zones as an economic hub with an investment of nearly 65 billion dollars by 2030. The study suggests that one-window operations could help the government and other people who work on the CPEC project understand how to run the project smoothly.